Respuesta :
For this case, we must simplify the following equation:
[tex]6x-7y = 2 (x + 10y)[/tex]
We apply distributive property to the terms of the parenthesis on the right side of the equation:
[tex]6x-7y = 2x + 20y[/tex]
We subtract "2x" on both sides of the equation:
[tex]6x-2x-7y = 2x-2x + 20y\\4x-7y = 20y[/tex]
We add "7y" to both sides of the equation:
[tex]4x-7y + 7y = 20y + 7y\\4x = 27y[/tex]
We clear one of the variables:
[tex]y = \frac {4x} {27}[/tex]
Answer:
[tex]y = \frac {4x} {27}[/tex]